TRANSFORMASI ADMINISTRASI SEKOLAH DENGAN PEMANFAATAN CANVA UNTUK PENGURUS ORGANISASI SMK NEGERI 1 CIMAHI - Nistrina, Khilda; Sukiman, Sukiman; Anggara, Mohammad Bayu; Rosmalina, Rosmalina; Anzani, Elvira Aprilia (Forum Komunikasi Dosen, 2024)
This Community Service Program (PKM) aims to enhance the digital administrative skills of student organization leaders at SMK Negeri 1 Cimahi. The main issue faced by the participants is their limited ability to manage administrative tasks using technology, which calls for a practical and relevant solution. The training was designed to introduce and train participants in using Canva, a digital application that supports professional administrative design. The method used was a participatory approach with stages of preparation, implementation, and evaluation. The training involved 30 participants and was conducted in three sessions: an introduction to Canva features, a demonstration of its use, and hands-on practice with guidance from the organizing team. Evaluation was carried out through observation and feedback surveys to assess participants' understanding and skills. The results show that 90% of participants were able to apply the training material effectively, such as creating reports and posters. Additionally, participants provided positive feedback, considering the training helpful in understanding and practicing technology-based administration. Therefore, this activity not only enhanced students' technical competencies but also provided long-term benefits for school organization management and prepared students for the digital era.